2018
DOI: 10.1371/journal.pone.0204163
|View full text |Cite
|
Sign up to set email alerts
|

Portal venous velocity affects liver regeneration after right lobe living donor hepatectomy

Abstract: ObjectivesWe investigated whether chronological changes in portal flow and clinical factors play a role in the liver regeneration (LR) process after right donor-hepatectomy.Materials and methodsParticipants in this prospective study comprised 58 donors who underwent right donor-hepatectomy during the period February 2014 to February 2015 at a single medical institution. LR was estimated using two equations: remnant left liver (RLL) growth (%) and liver volumetric recovery (LVR) (%). Donors were classified into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Therefore, portal blood flow is among the most crucial factors needed to launch the liver regeneration process. 45 After PH, hemodynamic changes in the portal vein (not affecting hepatic arteries) elevate the portal contribution per unit of liver tissue. The increased portal contribution increases the availability of growth factors and cytokines from the intestine and pancreas.…”
Section: Role Of Insulin In Liver Regeneration After Inhibiting Portal Blood Flowmentioning
confidence: 99%
“…Therefore, portal blood flow is among the most crucial factors needed to launch the liver regeneration process. 45 After PH, hemodynamic changes in the portal vein (not affecting hepatic arteries) elevate the portal contribution per unit of liver tissue. The increased portal contribution increases the availability of growth factors and cytokines from the intestine and pancreas.…”
Section: Role Of Insulin In Liver Regeneration After Inhibiting Portal Blood Flowmentioning
confidence: 99%
“…Several studies have been conducted to identify factors that may influence liver regeneration after donor hepatectomy [8,9,13]. The incidence of postoperative major complications after liver donation in older donors was significantly higher than that of younger donors [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of liver regeneration varies from individual to individual, even with similar types of resections considered for each living donor. Older age, male sex, high body mass index (BMI), preoperative alanine aminotransferase (ALT), and the presence of moderate or severe steatosis, have been reported to have a significant negative impact on postoperative liver regeneration in previous studies [8,9]. Therefore, it would be very important to identify the clinical factors related to liver regeneration, especially in living donors with a RTVR < 30%, to prevent postoperative liver insufficiency causing catastrophic events.…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment of patients after major liver resection, branched-chain amino acids with parenteral nutrition promotes hepatocyte proliferation and improves liver regeneration and function [12][13][14]. In living donor after hepatectomy studies, significant rapid regeneration was observed in small-RLV groups, in males, and in younger patients [6][7][8]15]. However, there was no significant difference in regeneration when comparing mild steatosis and no steatosis groups and when comparing right-lobe hepatectomy and left-lobe hepatectomy groups [6,10].…”
Section: Discussionmentioning
confidence: 99%